Changing clinical practice: views about the management of adult asthma. Issue 4 (1st December 1999) - Dawson, S; Sutherland, K; Dopson, S; Miller, R
Abstract : A case study of clinical practice in adult asthma is presented. The case is part of a larger project, funded by the North Thames NHS Executive Research and Development Programme, that sought to explore the part played by clinicians in the implementation of research and development into practice in two areas: adult asthma and glue ear in children. The first case of glue ear in children was reported in a previous issue of this journal (Quality in Health Care 1999;8:99-107). Background information from secondary sources on the condition, treatment, and organisation and location of care is followed by an account of the results of semistructured interviews with 159 clinicians. The findings are reported in two sections: clinical management and the organisation of care, and clinicians' accounts of what, why, and how they introduce changes into their practice. The way clinicians talk about their learning, their expressed views on acceptable practice, and their willingness to change were shown to be informed by construction of legitimate and sufficient evidence, respected colleagues, and accumulated individual experience. There was little open acknowledgment of the influence of organisational factors in influencing practice. To investigate whether relationships between task performance and organisational arrangements found in other sectors apply to UK health, more robust measures by which performance can be evaluated are needed.